ANALISIS FAKTOR-FAKTOR PENYEBAB STRES KERJA PERAWAT (DARI SUDUT PANDANG ERGONOMI) DI RUMAH SAKIT SYAFIRA KOTA PEKANBARU - Yesmianti '; Samsir '; Rio J M Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to take effect on the caused by the independent variable that consists of Workload, Individual Role in Organization and Personality One of the Nurses Job Stress. This study uses census or sample saturated. This method mengisisyaratkan all members of the sample population as sample, due to the limited number of samples. So in this research, the sample is the entire population of 97 respondents. The method used in this research is multiple linear regression to analyze the effect of partial and simultaneous with SPSS (version 17.0). From the testing that has been done, simultaneous test (F test) showed that Workload, Dlama Individual Role of the Organization, and Personality Someone together have a significant effect on Nurses Job Stress. Partial test (t test) showed that Workload has the most influence kuatter the Nurses Job Stress, whereas Individual Role in Organization and Personality One need to have an influence on Nurses Job Stress. The magnitude of the effect that the (R ^ 2) by these three independent variables together against the dependent variable of 49.1% while the remaining 50.9% is influenced by other variables that are not included in this study.Keywords : Job Stress, Workload, Individual Role In Organization, and One’s Personality.